The Collective Soul - Barak, Uriel (The journal of Jewish thought & philosophy, 2016)
This article examines R. Zvi Yehudah Kook’s reading of two earlier thinkers who were influential in the formulation of his thought—the Maharal of Prague and R. Avraham Azulai. I argue that his creative and unique reading of these texts exemplifies a fascinating dialogue he held with earlier sources, which he interpreted and infused with his own theological postulates. Here I explore his theory of the unique nature of the Jewish soul, in both its collective and individual manifestations. The connection between R. Zvi Yehudah’s approach to interpreting earlier Jewish theological texts and that of his father, R. Avraham Itzhak HaCohen Kook, will also be discussed.